Sequential Fermentation with Non-Saccharomyces Yeasts Improves the Chemical and Sensory Characteristics of Albariño and Lado Wines - Estefanía García-Luque; Rebeca González; Rafael Cao; Elvira Soto; Pilar Blanco (Fermentation)
The application of non-Saccharomyces yeast in mixed fermentations with Saccharomyces cerevisiae is a useful tool to enhance wine quality. In this study, Metschnikowia fructicola Mf278 and Pichia kluyveri Pk1 were used in sequential fermentations with S. cerevisiae XG3 to ferment grape musts from Albariño and Lado. The development of fermentations was monitored by daily measurements of density and temperature, and sampling at the beginning, tumultuous, and final stages for microbiological control. The basic chemical parameters of wine were determined using the OIV official methodology, whereas the fermentative aroma compounds were quantified by GC–MS. M. fructicola Mf278 and P. kluyveri Pk1 were the predominant yeasts at the initial stages of sequential fermentations but, after the addition of S. cerevisiae XG3, they rapidly declined. A codominance of different S. cerevisiae strains was observed at the middle and final stages of fermentation. At the chemical level, Mf278 lowered the volatile acidity and increased the glycerol content of wines. Moreover, M. Mf278 and Pk1 increased the content of fermentative esters and fatty acids of wines. These compounds contribute fruity and floral notes to the wines that stood out over wines made only with S. cerevisiae, and were better valued at the sensory level.